News Text Learning With Tribunnews Instagram Account for 8th Grade Students - Anita Dwi Berlian Putri; I Nengah Martha; Kadek Wirahyuni (Journal of Digital Learning and Education, 2022)
Online learning frequently employs tedious media, including news text learning. This study aims to describe the innovative use of learning media in class VIII B learning of news texts using the Tribunnews Instagram account at SMP 17 Agustus – 1 Muncar. This research is qualitative because the data are presented in the form of words. The method of research employed is descriptive research. The subjects of this study were eighth-grade B SMP 17 Agustus-1 Muncar students. With Instagram Tribunnews, the objective is to learn news text. Documentation is the technique used for data collection. The data processing technique used is a qualitative descriptive technique. The findings of this study indicate that learning with Instagram Tribunnews video media is superior and more engaging for students than learning with news sample text media alone. This can be seen in the improvement of student interactions over time. There were only students who did not have access to a reliable network, and there were students who were late for Zoom. However, the teacher has provided a solution for this.